Effect of Various Defects on 4H-SiC Schottky Diode Performance and Its Relation to Epitaxial Growth Conditions - Jinlan Li; Chenxu Meng; Le Yu; Yun Li; Feng Yan; Ping Han; Xiaoli Ji (Micromachines, 2020)
In this paper, the chemical vapor deposition (CVD) processing for 4H-SiC epilayer is investigated with particular emphasis on the defects and the noise properties. It is experimentally found that the process parameters of C/Si ratio strongly affect the surface roughness of epilayers and the density of triangular defects (TDs), while no direct correlation between the C/Si ratio and the deep level defect Z1/2 could be confirmed. By adjusting the C/Si ratio, a decrease of several orders of magnitudes in the noise level for the 4H-SiC Schottky barrier diodes (SBDs) could be achieved attributing to the improved epilayer quality with low TD density and low surface roughness. The work should provide a helpful clue for further improving the device performance of both the 4H-SiC SBDs and the Schottky barrier ultraviolet photodetectors fabricated on commercial 4H-SiC wafers.